Validation of the English and simplified Mandarin versions of the Fear of Progression Questionnaire - Short Form in Chinese cancer survivors - Mahendran, Rathi (2021)
Background: The fear of illness progression is common amongst those with chronic illnesses including cancers, and contributes to high psychological morbidity. Research in Asia on such fears however, is limited by a paucity of validated measurement instruments. Amongst the many available instruments, the Fear of Progression Questionnaire has a high quality rating, an important consideration in its selection. This study developed a simplified Mandarin version of the Fear of Progression Questionnaire - Short Form (FoP-Q-SF), and validated the English and Mandarin versions for use in Chinese populations. Methods: The translation to a simplified Mandarin version was through a forward-backward translation with emphasis on conceptual and cultural equivalence. Cancer survivors (N= 341) completed a self-report questionnaire,the Fear of Progression Questionnaire–Short Form, other measures of fear of progression, depression, anxiety, and quality of life. Reliability and criterion validity were assessed, and the factor-structure was replicated with a confirmatory factor analysis. Results: The Fear of Progression Questionnaire–Short Form demonstrated high internal and test-retest reliability.Criterion validity was also demonstrated through convergent, concurrent and discriminant validity. The factor structure was supported and replicated. The goodness-of-fit indices of the original model indicated some misfit,which could be adequately addressed by freeing five parameters in the error covariance matrix, without changing the one-factor structure. Conclusions: The Fear of Progression Questionnaire–Short Form is a reliable and valid measure of fear of progression applicable to a mixed-cancer survivor population in Singapore. The simplified Mandarin version of the questionnaire will be useful in other parts of Asia and for Chinese migrants in the West, further extending the use of this questionnaire.